Constraints Perceived by the Vegetable Growers towards Excessive Use of Chemicals in Bankura District of West Bengal (Indian Journal of Extension Education, 2021)
The study was conducted during 2018 to know the constraints perceived by the vegetable growers towards excessive use of chemicals in the Bankura district of West Bengal. This study was followed ex-post and expletory research design with considering 27 constraints, which data was suitably analyses with the help of principal component analysis. The results of these 27 constraints were divided into six components on basis Eigen rules. The six components had greater than one Eigen value 6.265, 2.59, 2.292, 1.421, 1.216 and 1.086 respectively. The first component having Eigenvalue of 6.265 was labeled as Protection Knowledge. Similarly other sequentially components were labeled as Lack of Knowledge, Bio - control, Scarcity, Unavailability and Training respectively. The particular emphasis in this study was therefore on identifying the problems faced by vegetable growers in the application of pesticides to vegetable crops during the use of a chemical in the study area.